2016
DOI: 10.1093/femsec/fiw239
|View full text |Cite
|
Sign up to set email alerts
|

Depth-dependent influence of different land-use systems on bacterial biogeography

Abstract: Despite progress in understanding microbial biogeography of surface soils, few studies have investigated depth-dependent distributions of terrestrial microorganisms in subsoils. We leveraged high-throughput sequencing of 16S rRNA genes obtained from soils collected from the RARE: Charitable Research Reserve (Cambridge, ON, Canada) to assess the influence of depth on bacterial communities across various land-use types. Although bacterial communities were strongly influenced by depth across all sites, the magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 92 publications
7
46
1
Order By: Relevance
“…This is not a trivial assumption: Mounting evidence indicates soil biota compositions vary widely across small spatial scales due to dispersal processes, soil physicochemical properties, soil water content, and other factors (Monard et al 2016, Zhang et al 2016, Ping et al 2017, Seuradge et al 2017). This is not a trivial assumption: Mounting evidence indicates soil biota compositions vary widely across small spatial scales due to dispersal processes, soil physicochemical properties, soil water content, and other factors (Monard et al 2016, Zhang et al 2016, Ping et al 2017, Seuradge et al 2017).…”
Section: Ensure Analyses Of Ratio Data Meet Statistical Assumptions mentioning
confidence: 99%
See 2 more Smart Citations
“…This is not a trivial assumption: Mounting evidence indicates soil biota compositions vary widely across small spatial scales due to dispersal processes, soil physicochemical properties, soil water content, and other factors (Monard et al 2016, Zhang et al 2016, Ping et al 2017, Seuradge et al 2017). This is not a trivial assumption: Mounting evidence indicates soil biota compositions vary widely across small spatial scales due to dispersal processes, soil physicochemical properties, soil water content, and other factors (Monard et al 2016, Zhang et al 2016, Ping et al 2017, Seuradge et al 2017).…”
Section: Ensure Analyses Of Ratio Data Meet Statistical Assumptions mentioning
confidence: 99%
“…Combining soil samples by NAS and species prevented Teste et al from confirming step 1. Soil microbe compositions can vary widely across small spatial scales (Monard et al 2016, Zhang et al 2016, Ping et al 2017, Seuradge et al 2017, Wang et al 2017, so some sampled microbial species may have occurred near just one or a few field plants. Even microbes occurring near a single plant would presumably be distributed to 20 conspecific glasshouse pots and ≥150 NAS mixture pots (Appendix S1: Fig.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Declining carbon substrate availability with soil depth produces oligotrophic environment at depth, which may restrict bacterial activity and promote subsurface-dwelling groups capable of utilizing recalcitrant carbon sources (35, 36). Previous studies have shown that soil bacterial diversity is typically highest in the topsoil and decreases with soil depth (34, 37). However, the diversity or abundance of different bacterial phyla may decrease (36, 37), increase (38), or remain consistent (34) along soil profile.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown that soil bacterial diversity is typically highest in the topsoil and decreases with soil depth (34, 37). However, the diversity or abundance of different bacterial phyla may decrease (36, 37), increase (38), or remain consistent (34) along soil profile. Compared with bacteria, soil archaeal diversity patterns are much less explored at depth.…”
Section: Introductionmentioning
confidence: 98%